PEMBELAJARAN BERBASIS MASALAH MELALUI THINK PAIR SHARE TERHADAP HASIL BELAJAR BIOLOGI DAN RETENSI SISWA - Eva Nurul Malahayati (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2016)
This article examines the effect of problem-based instruction using Think-Pair-Share strategy towards learning achievement on biology subject and retention of students with high and low academic performance. This study used quasi experiment implementing Nonrandomized Control Group Pretest-Postest of 2x2 factorial design. Sample of this study were 70 students of 10th graders of SMAN 4 Malang representing high academic performance and 70 students of 10thgraders of SMA Maarif Singosari representing low academic performance. Data were analyzed using descriptive statistics and Anacova Test. The study revealed that problem-based instruction with TPS did not significantly improve students achievement in Bilology subject, but academic potential affects significantly on students retention.